2019
DOI: 10.1159/000495852
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Metabolically Healthy and Unhealthy Obesity according to Different Criteria

Abstract: Objective: Obesity-related disease risks may vary depending on whether the subject has metabolically healthy obesity (MHO) or metabolically unhealthy obesity (MUO). At least 5 definitions/criteria of obesity and metabolic disorders have been documented in the literature, yielding uncertainties in a reliable international comparison of obesity phenotype prevalence. This report aims to compare differences in MHO and MUO prevalence according to the 5 most frequently used definitions. Methods: A random sample of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 49 publications
5
50
4
2
Order By: Relevance
“…The prevalence of MHO ranges from 1•1 to 28•5 % in different populations (30) . The prevalence of MHO we reported in our rural Chinese adults was obviously lower than that in previous studies because of the strictness of the metabolically healthy definition (16,31) . By contrast, the proportions of metabolically unhealthy individuals with or without obesity were relatively higher, which indicates the need for making interventional strategies to ensure that people are metabolically healthy in rural China.…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of MHO ranges from 1•1 to 28•5 % in different populations (30) . The prevalence of MHO we reported in our rural Chinese adults was obviously lower than that in previous studies because of the strictness of the metabolically healthy definition (16,31) . By contrast, the proportions of metabolically unhealthy individuals with or without obesity were relatively higher, which indicates the need for making interventional strategies to ensure that people are metabolically healthy in rural China.…”
Section: Discussioncontrasting
confidence: 87%
“…In total 10% defined as MH obese is among the highest prevalence independent of criteria used for metabolic health summarized by Liu et al [40] and Wildman et al [41]. Using BMI rather than waist circumference to define obesity often yields higher prevalence of MH obese [40]. Yet, other studies have found comparable prevalence of MH obese as the present study using ≥2 criteria for metabolic health [42].…”
Section: Discussionsupporting
confidence: 46%
“…It is however possible that our study population is healthier than other populations. In total 10% defined as MH obese is among the highest prevalence independent of criteria used for metabolic health summarized by Liu et al [40] and Wildman et al [41]. Using BMI rather than waist circumference to define obesity often yields higher prevalence of MH obese [40].…”
Section: Discussionmentioning
confidence: 99%
“…A CRF ( · VO 2max in mL·kg −1 ·min −1 ) reference value lower than the 50th percentile was used as the cut-off point, according to the FRIEND Registry [29]. The definition of the MUO and the MHO phenotypes were obtained based on the joint combination of obesity markers (i.e., BMI) and cardiometabolic abnormalities, taking into account the following definitions: the National Cholesterol Education Program-Adults Treatment Panel III, Wildman, Wildman Modified and Ortega [4,5,30].…”
Section: Measurementsmentioning
confidence: 99%